Gestión educativa y vinculación comunitaria en el centro educativo comunitario intercultural bilingüe de educación básica “Sergio Núñez” de la comunidad de michacalá, parroquia Zumbahua en el año lectivo 2015 -2016. - Latacunga Pilatasig, María Eloysa (2016)
One of the most important aspects in the society is the children education; the integral formation we want them to receive, it has to be in an atmosphere of conviviality and appropriate linkages between members of the institution and parents, so improving the work between educational trilogy take to improve learning rates of the educational community, The idea came from the visible flaws in teachers, students and parents, which perform theirs activities individually with lack of tolerance, dialogue, friendship, respect, among others. So that, the main purpose of this research is to design an Educational Management Strategy to improve the levels of community engagement in The Intercultural Bilingual Community Educational Center "Sergio Nunez". For this research study, an understanding and analysis work of the educational population of the institution was conducted through surveys and interviews on how to address the education management and community engagement, as it is thought that the feelings, experiences and direct contact with teachers, parents, students, administrative and the context provide answers that are needed to strengthen educational management Thus, with the support of the obtained information it was possible to design a based strategy on the interpersonal and Administrative management. Thus, with the support of the obtained information it was possible to design a based strategy on the interpersonal and Administrative management that look for the Leadership through the dialogue and the community engagement.